The importance of non-formal education for the economy of Serbia - Šormaz Goran (Trendovi u Poslovanju)
Adult learning and education are an important component of the lifelong learning process, integrating different forms and programs of non-formal and informal learning. This area of learning encompasses a variety of content, from literacy and general skills, through vocational education and training content, to family, civic, environmental, media, leisure education, and many other areas whose priorities depend on the specific needs of each country . The formal system does not meet the needs of the individual or community to learn. Due to the inability of formal education to monitor changes in education resulting from the rapid development of science and technology, as well as economic and social changes, informal education has emerged. This education is an essential and necessary complement to formal education. Non-formal education is defined as any organized educational activity outside the existing formal system, which serves specific users and learning objectives. Non-formal education is provided through activities such as courses, seminars, lectures, conferences, workshops, various types of training, as well as volunteering. The field of non-formal education is very important in Serbia, it enables persons who have not completed formal education or have finished school with which they cannot find a job in the profession, to actually retrain in the process of non-formal education to perform some of the more demanding jobs, or to apply for a job in Serbia, or looking for a job abroad.